PENERAPAN MODEL PEMBELAJARAN SAVI SEBAGAI UPAYA MENINGKATKAN KETERAMPILAN MENULIS SISWA KELAS VIII DI SMPN 1 PANGKAJENE : APPLICATION OF THE SAVI LEARNING MODEL AS AN EFFORT TO IMPROVE THE WRITING SKILLS OF EIGHTH GRADE STUDENTS AT SMPN 1 PANGKAJENE - Siti Rezki Hardianti; Ramly; Baharman (Journal of Applied Linguistics and Literature, 2026)
This study is a classroom action research project aimed at describing the learning process and outcomes of students’ poetry writing skills using the SAVI Learning Model with Year 8 students in Hukmawaty’s class at SMPN 1 Pangkajene. The study was conducted over two cycles, preceded by a pre-cycle phase. The data collection techniques used were: observation, interviews, documentation, and tests. The results of the study indicate that students’ poetry writing test scores in the pre-cycle phase were 24.13%, falling into the ‘poor’ category and failing to meet the Minimum Passing Criteria (KKM). In Cycle I, the results were 82.75% in the ‘good’ category, and in Cycle II, students’ poetry writing scores reached 100% in the ‘very good’ category. Student scores improved by 75.87% from the start of the pre-cycle to the implementation of Cycle II. Based on this, it can be concluded that the application of the SAVI Learning Model can improve students’ poetry writing skills